Increased anxiety from fear of Omicron in China as compared to North America and Western Europe: A cross-sectional Kendall’s tau-b analysis using the generalized anxiety disorder 7-item questionnaire - Shan, Dan; Liu, Chang; Li, Shaoyang; Zheng, Yuandian (Frontiers in Psychiatry, 2022)
Background Policies dealing with the Coronavirus Disease 2019 (COVID-19) pandemic vary across the globe, the different governmental responses then affect the public perception of COVID-19. Many unofficial Chinese media outlets frequently spread misinformation about COVID-19 and exaggerated reports of rare sequelae of Omicron for monetization and attention seeking, leading to panics in the Chinese public. In comparison the attitudes toward Omicron in other countries around the world, especially in North America and Western Europe have shifted to a more relaxed stance. Objective This article primarily aims to investigate the association between Chinese people’s attitudes toward the potential after-effects of Omicron and their anxiety status, as compared to these of people living in North America or Western Europe. Methods We conducted a questionnaire survey via the Credamo and collected valid data from 500 Chinese (not living in Shanghai), another 500 Chinese (living in Shanghai) and 500 people living in North America or Western Europe in June 2022. Kendall’s coefficient of rank correlation tau-sub-b was used to examine this association. Results The results suggested that subjective attitudes of Chinese participants toward the sequelae of Omicron were positively and significantly associated with their anxiety status [i.e., the Generalized Anxiety Disorder 7-item (GAD-7) scores] in Shanghai (China) (Tb = 0.44, p < 0.01) and other parts of China outside Shanghai (Tb = 0.37, p < 0.01). However, no such significant correlation was found in North America & Western Europe (Tb = -0.01, p > 0.05). Conclusion Our findings showed that Chinese participants who were more worried about the after-effects of Omicron had higher levels of anxiety. Although it is true that Long COVID-19 should be a concern, exaggerated media reporting can impact negatively on an individual’s mental wellbeing. Only through the dissemination of robust scientific studies, the misinformation and the fears that follow it can be put to rest.